Catholicism and the American Experience: Portsmouth Review - MacGuire, James P. (Rowman & Littlefield Publishers, 2014)
What does it mean to be Catholic in America? Catholicism and the American Experience features essays from Robert George, Peter Steinfels, George Weigel, E. J. Dionne, and many more, exploring the unique elements of American Catholicism. The volume highlights the proceedings of the fifth annual Portsmouth Institute conference. This collection of essays addresses the topic of Catholicism and the American Experience from diverse points of view. They discuss thorny topics such as the relationship between the Patient Protection and Affordable Care Act and religious freedom, what it means to be Catholic in a secular age, and the current state of Catholic art. Essays also explore subjects ranging from New Evangelization in the church to Catholic leadership.